Kajian Rainbow 2-Connected Pada Graf Eksponensial dan Beberapa Operasi Graf - Herninda Lucky Oktaviana; Ika Hesti Agustin; Dafik Dafik (jcgant, 2021)
Let G=(V(G),E(G)) is a graph connected non-trivial. Rainbow connection is edge coloring on the graph defined as f:E(G)→ {1,2,...,r|r N}, for every two distinct vertices in G have at least one rainbow path. The graph G says rainbow connected if every two vertices are different in G associated with rainbow path. A path u-v in G says rainbow path if there are no two edges in the trajectory of the same color. The edge coloring sisi cause G to be rainbow connected called rainbow coloring. Minimum coloring in a graph G called rainbow connection number which is denoted by rc(G). If the graph G has at least two disjoint rainbow path connecting two distinct vertices in G. So graph G is called rainbow 2-connected which is denoted by rc_2(G). The purpose of this research is to determine rainbow 2-connected of some resulting graph operations. This research study rainbow 2-connected on the graph (C_4^K_n and Wd_(3,2)K_n).